Analysis of Factors Influencing the Mechanical Properties of Flat PolyJet Manufactured Parts. (2015) - Gay, P.; Blanco, D.; Pelayo, F.; Noriega, A.; Fernández, P.
Abstract: In Additive Manufacturing (AM), parts are manufactured layer-upon-layer. This strategy affects the mechanical properties of AM parts, since they cannot just be assimilated to those of parts manufactured by traditional methods. The PolyJet AM technology uses UV energy to cure layers of photopolymer that are stacked one on top of the following. The amount of energy that reaches each layer is related to several aspects of the manufacturing procedure, such as jetting head displacement strategy or UV irradiation pattern. This work aims to analyse the relative influence of configuration parameters on the relaxation modulus E(t) of flat parts manufactured using PolyJet technology and orientated on the XY plane. Evolution of material properties with respect to time has been used since parts shall present viscoelastic behaviour. Four factors have been evaluated: part spacing along X axis (Δx) and along the Y axis (Δy), orientation of the part within the tray (φ) and surface quality (Q). Influence of Q has been included since material properties could be modified by UV shielding effect. Experimental results have pointed out that Y-spacing and orientation φ both affect E(t).